Je antiselekční počínání v reprodukční medicíně antibiologické? - Doležal, Antonín; Šťastná, S; Plavka, Richard (Česká gynekologie, 1997)
The human reproduction has the monotocial element of K strategy (nidifungous) with mature newborn mammals and also of the r strategy (nidiculous) with immature mammals. There are questions about „contra naturam" antiselective practice in the treatment of extremely premature newborns. Allometric equations were calculated form 93 species of mammals: Mneo = 0.03374 M 0.946 and Gt = 68.536 M 0.225 (Mneo is the body weight of newborns in kg, M is the body weight of the female in kg and Gt is the gestational period in days). According to these allometric equations the birthweight of newborns is from 1100 g to 1600 g and gestational age is from 22.4 - 24. 5 weeks of gestation. The data from comparative zoology are in conformity with requirements of neonatologists to receive prematurity without further intra intrauterine pathologies. The postnatal care taken after extremely premature newborns replaces adaptive mechanisms which are present in immature mammalian newborns of r strategy. The neonatological practice has decreased the viability level to 24 weeks of gestation during the last 20 years. Further lowering to 22 weeks is possible in the near future.
Keywords: Fetal Organ Maturity; dospělí; Neonatology; Female; dítě; novorozenec; Adult; ženské pohlaví; selekce (genetika); lidé; Infant, Newborn; těhotenství; Selection, Genetic; reprodukční lékařství; neonatologie; Child; Reproductive Medicine; Pregnancy; zralost orgánů plodu; Humans